Status keluarga Malaysia dalam perspektif kualiti - Rika Fatimah; P.L ;Jemain .A.A (Universiti Kebangsaan Malaysia, 2009)
The well being of a family, whether its good or bad, is reflected to its society. Family, as an organisation, is a source for producing human capital with certain standard quality. Therefore, it is important to continously improve the quality of family. The aim of this study is to investigate the quality of satisfaction and performance of family life among Malaysians. This effort would help to identify the measures that need to be prioritised for the improvement of family life. To measure the quality of family performance, quality based approaches based on certain well known theory such as customer satisfaction and organisational performance are utilized. Samples involved 1,213 respondents, who are married and have children, are selected from Peninsular Malaysia. Three dimensions that have been identified as important parameters for assessing family performance are family relationship, family development and family sustainability. The result shows that family sustainability (43.2%) has strong influenced to the status of dissatisfaction in family. Furthermore, family development (37.3%) has major influenced towards performance in family. In this study, the two quality based approaches are used to analyse the responses of respondent in determining the priorities for improvement on quality of family.